2017
DOI: 10.1093/bioinformatics/btx005
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the trees through the forest: sequence-based homo- and heteromeric protein-protein interaction sites prediction using random forest

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(140 citation statements)
references
References 46 publications
5
135
0
Order By: Relevance
“…By implementing these features, we trained our sequence-based protein interface predictors using both homomeric and heteromeric protein interaction datasets. Predictions were significantly more accurate than other predictors on the same test-sets (Hou et al, 2017).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…By implementing these features, we trained our sequence-based protein interface predictors using both homomeric and heteromeric protein interaction datasets. Predictions were significantly more accurate than other predictors on the same test-sets (Hou et al, 2017).…”
Section: Introductionmentioning
confidence: 84%
“…The webserver provides a 'remastered' version of our previous approach (Hou et al, 2017) which improves the speed of the process by deriving sequence conservation profiles for the homologues by remastering the blast profile of the input sequence (Simossis and Heringa, 2004). The procedure is described in more detail in Supplementary Section S2, see also Supplementary Figure S2.…”
Section: The Serendip Webservermentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that the values of six measures achieved in these three independent benchmark datasets are lower than that in the dataset used in this work, but it is reasonable because the IHT-XGB model is built on this original dataset. Table 4 also shows the prediction performance of five models, i.e., SSWRF, LORIS, PSIVER, SCRIBER, and DELPHI, in identification of protein-protein interaction sites [31][32][33][34][35][36][37]. The highest results in each performance measures for different models are highlighted as bold type.…”
Section: Prediction Performance In Independent Benchmark Datasetsmentioning
confidence: 99%
“…Theoretically, the strength of a protein-protein interaction can be characterized by a dissociation constant K D = k d /k a , where k d is the dissociation rate constant and k a is the association rate constant. Many commonly used techniques provide measurements of K D , which can be calculated by the concentration of free proteins, but most of them do not offer the real-time measurements of k d and k a [34].…”
Section: Limits Of Prediction Validationmentioning
confidence: 99%